2008
DOI: 10.2174/157016208784325010
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Residual Viremia and Proviral DNA in Patients with Suppressed Plasma Viral Load ( < 400 HIV-RNA cp/ml) During Different Antiretroviral Regimens

Abstract: Low levels of plasma viremia (below 50 copies/ml of HIV-1 RNA) can be detected in the majority of HIV+ subjects successfully treated with HAART. Aim of our study was to evaluate the impact of different antiretroviral regimens on this residual viremia and on proviral HIV-1 DNA in HAART-treated subjects with plasma HIV RNA <400 cp/ml and no history of virological failure. To this purpose, a cross-sectional analysis of 319 HIV-positive patients on HAART with plasma HIV RNA <400 cp/ml was performed. Subjects had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 22 publications
(27 reference statements)
0
20
2
1
Order By: Relevance
“…More potent effects on residual viremia have been demonstrated with the use of NNRTIs than with protease inhibitors (5,21), and a better performance of nevirapine than efavirenz has been suggested (5,13). In this study, no significant association was demonstrated between HAART composition and undetectable levels of HIV DNA.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…More potent effects on residual viremia have been demonstrated with the use of NNRTIs than with protease inhibitors (5,21), and a better performance of nevirapine than efavirenz has been suggested (5,13). In this study, no significant association was demonstrated between HAART composition and undetectable levels of HIV DNA.…”
Section: Discussionmentioning
confidence: 51%
“…The real-time TaqMan protocol published by Viard and colleagues (29) was used to quantify the cellular HIV DNA copy number in PBMCs. The cell line 8E5, which contains one copy of integrated HIV DNA in each cell, was used to build a standard curve, with a sensitivity of 5 copies/million PBMCs (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, i. MRV can persist for years despite of suppressive ART 4 ; ii. different ART regimens may suppress MRV at different levels 18,25,26 and the patient susceptibility to certain HIV inhibitors seems to be different, depending also on HIV-1 subtypes, previous antiretroviral experience and duration of HIV-infection 27 ; iii. intensification of ART generally does not abolish MRV 12,23,24,28 ; iv.…”
Section: Discussionmentioning
confidence: 99%
“…The real-time TaqMan protocol was used to quantify the cellular HIV DNA copy number in PBMCs as previously described [20]. The cell line 8E5, which contains one copy of integrated HIV DNA in each cell, was used to build a standard curve with a sensitivity of 5 copies/million PBMCs [21]. …”
Section: Methodsmentioning
confidence: 99%